PENGARUH PENGGUNAAN APLIKASI MEDIA PEMBELAJARAN DIGITAL TERHADAP KREATIVITAS MAHASISWA PROGRAM STUDI PPKN UNIVERSITAS RIAU - Pramesti, Aulia Ayu; Gimin; Supentri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the effect of using digital learning media applications on the creativity of students of the Pancasila and Civics Education (PPKn) Study Program at Riau University. The background of the research is based on the transformation of the higher education landscape due to the development of digital technology, which encourages students to utilize technology to create innovative learning media. This phenomenon raises questions about the extent to which the use of digital learning media can influence and develop student creativity. This research uses a descriptive quantitative research method. The research population was all students of the Civics Study Program at Riau University class of 2021, 2022, and 2023. The research stages include the preparation of questionnaire instruments, data collection from 100 students selected using random sampling techniques, and data analysis. Data analysis was carried out using a simple linear regression test with the help of the SPSS version 25 program, after going through the classical assumption test (normality, and linearity). The results showed that there was a positive and significant effect of using digital learning media applications on student creativity. This is evidenced by the coefficient of determination (R2) of 0.581, which indicates that 58.1% of variations in student creativity are explained by the use of digital learning media. The implication of this research is the importance of integrating digital learning media.